Increasing the Students’ Awareness of Stressed Syllable in Pronouncing English Words - Anggara Jatu Kusumawati (Universitas Ahmad Dahlan, 2017)
This study explores how to increase the students’ awareness of stressed syllable in pronouncing English words based on activity-based approach. The approach in this research employs traditional techniques which consist of IPA habituation, drills, and stress marking. The research involved 32 selected sophomore students majoring in English. The research was carried out quantitatively by providing the students with 61 words containing stressed syllable prior and post class treatment in the fom of pre and post test. The findings pinpoint the improvement of students’ pronunciation. Given the result of the post-test, it comes to light that all of the students have better pronunciation and better ability for syllable stressing.